THE INFLUENCE OF EMOTIONAL INTELLIGENCE AND SELF-EFFICACY ON THE CRITICAL THINKING SKILLS OF GRADE XI SOCIAL STUDIES STUDENTS AT SMAN 41 JAKARTA - Nur Aini Azizah; I Ketut R Sudiarditha; Aditya Pratama (Nindikayla Institute, 2023)
Critical thinking skill is a cognitive process involving one's mind to integrate its knowledge in analyzing information and determining solutions to existing problems according to data and facts to produce the right decisions. This study aimed to determine whether emotional intelligence and self efficacy affect the critical thinking skills of XI IPS students at SMA Negeri 41 Jakarta in ecnonimics subject. This research is a quantitative research with survey explanatory method. The sampling technique used is proportional random sampling with a sample of 84 class XI IPS SMA Negeri 41 Jakarta students. The data collection for emotional intelligence and self efficacy using a questionnaire, while the critical thinking skills using an objective assessment test. The results of this study indicate that emotional intelligence has a positive and significant effect on students critical thinking skills, self efficacy has a positive and significant effect on students critical thinking skills. Emotional intelligence and self efficacy simultaneously have a positive and significant effect on students critical thinking skills. The results of this study imply that students emotional intelligence and self efficacy can improve their critical thinking skills